Immune Response to SARS-CoV-2 Vaccines - Navya Bellamkonda; Upendra Pradeep Lambe; Sonali Sawant; Shyam Sundar Nandi; Chiranjib Chakraborty; Deepak Shukla (Biomedicines, 2022)
COVID-19 vaccines have been developed to confer immunity against the SARS-CoV-2 infection. Prior to the pandemic of COVID-19 which started in March 2020, there was a well-established understanding about the structure and pathogenesis of previously known Coronaviruses from the SARS and MERS outbreaks. In addition to this, vaccines for various Coronaviruses were available for veterinary use. This knowledge supported the creation of various vaccine platforms for SARS-CoV-2. Before COVID-19 there are no reports of a vaccine being developed in under a year and no vaccine for preventing coronavirus infection in humans had ever been developed. Approximately nine different technologies are being researched and developed at various levels in order to design an effective COVID-19 vaccine. As the spike protein of SARS-CoV-2 is responsible for generating substantial adaptive immune response, mostly all the vaccine candidates have been targeting the whole spike protein or epitopes of spike protein as a vaccine candidate. In this review, we have compiled the immune response to SARS-CoV-2 infection and followed by the mechanism of action of various vaccine platforms such as mRNA vaccines, Adenoviral vectored vaccine, inactivated virus vaccines and subunit vaccines in the market. In the end we have also summarized the various adjuvants used in the COVID-19 vaccine formulation.